(untitled) (Baghdad Science Journal, 2023)
In this study, an improved process was proposed for the synthesis of structure-controlled Cu2O nanoparticles, using a simplified wet chemical method at room temperature. A chemical solution route was established to synthesize Cu2O crystals with various sizes and morphologies. The structure, morphology, and optical properties of Cu2O nanoparticles were analyzed by X-ray diffraction, SEM (scanning electron microscope), and UV-Vis spectroscopy. By adjusting the aqueous mixture solutions of NaOH and NH2OH•HCl, the synthesis of Cu2O crystals with different morphology and size could be realized. Strangely, it was found that the change in the ratio of de-ionized water and NaOH aqueous solution led to the synthesis of Cu2O crystals of different sizes, while the morphology of Cu2O crystals was not affected. The synthesized Cu2O crystal samples were used as photocatalysts for methyl orange (MO) dye decomposition, as a model molecule, to evaluate the photocatalytic activities. However, under 200 watts of a visible light source, there are four samples with and without graphene-based nanocomposite of Cu2O NPs. The results showed that, compared with roughly spherical, irregular but thick plates, brick and small granule spheres shaped Cu2O nanoparticles provided better activity. The Cu2O sample with irregular but thick platelet-like shapes, having an average particle size of 0.53 µm, exhibited excellent photocatalytic activity (99.08% degradation). In addition, by reducing the size of Cu2O particles and preparing their graphene composition, one can fabricate a sample (Cu2-Cu2Gr) with the highest efficiency which has significantly better photocatalytic activity in comparison to the others. This work represents an innovative strategy for pre-the-case production of nanomaterials with shapes and sizes, that is, Cu2O crystals, with excellent photocatalytic activity through compositing with graphene